Pemetaan Kondisi Sanitasi Lingkungan Dasar Serta Risiko Penyakit Pada Pondok Pesantren Di Kota Surabaya - Widya Nilandita; Khuliyah Candraning Diyanah; Dedy Suprayogi (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2022)
Sanitation is the most important health-related aspect of public health and the environment. Aspects of environmental health in sanitation include community clean water facilities, waste management, waste management, and management of sanitation facilities. Islamic boarding schools are one of the institutions that have problems in sanitation, cases are often found related to students who are infected with several diseases. This study aims to map the sanitation conditions and the risk of disease in Islamic boarding schools in the city of Surabaya. This study uses the observation method for data collection, then analyzed by quantitative description. The sanitation conditions of Islamic boarding schools in Surabaya City from the aspect of clean water are in a good category 55.2%, 41.4% very good, and 3.4% less. Based on the waste aspect, the category result sufficient, less, good, and very good is 52%, 24%, 17%, and 7%, respectively. Furthermore, based on aspects of toilet and bathroom hygiene, the majority was very good, 82.8%, sufficient category was 13.8%, and the good category was 3.4%; and based on wastewater aspects, 100% Islamic boarding school was a very good category. In conclusion, the sanitation conditions of Islamic boarding schools in Surabaya City based on the waste aspect are sufficient; however, based on clean water, the hygiene aspects of toilets and bathrooms, and the aspect of wastewater are very good.